Poor Little Rich Kids? The Determinants of the Intergenerational Transmission of Wealth - Sandra E. Black; Paul J. Devereux; Petter Lundborg; Kaveh Majlesi (Institute for the Study of Labor (IZA), 2015)
Wealth is highly correlated between parents and their children; however, little is known about the extent to which these relationships are genetic or determined by environmental factors. We use administrative data on the net wealth of a large sample of Swedish adoptees merged with similar information for their biological and adoptive parents. Comparing the relationship between the wealth of adopted and biological parents and that of the adopted child, we find that, even prior to any inheritance, there is a substantial role for environment and a much smaller role for genetics. We also examine the role played by bequests and find that, when they are taken into account, the role of adoptive parental wealth becomes much stronger. Our findings suggest that wealth transmission is not primarily because children from wealthier families are inherently more talented or more able but that, even in relatively egalitarian Sweden, wealth begets wealth.
Keywords: G11; J01; J13; J62; 330; intergenerational mobility; nature versus nurture; portfolio allocation